2003
DOI: 10.1103/physrevb.68.155428
|View full text |Cite|
|
Sign up to set email alerts
|

High-bias conductance of atom-sized Al contacts

Abstract: We measured the high-bias conductance of atom-sized Al contacts at room temperature for biases from 0.1 to 0.8 V, and studied the formation probability and the lifetime of Al single-atom contacts ͑SACs͒ under high biases. Analyses of conductance plateaus corresponding to Al SACs revealed that the formation probability of SACs decreases with increasing the bias and leads to the suppression of the first peak in the conductance histogram. The formation probability vanishes at a critical bias V bc ϳ0.8 V. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Most notably, our simulations reproduce the sequence of critical voltages observed experimentally. These experimental findings are furthermore in accordance with earlier observations showing how Au single atom wide contacts [7,27] can withstand voltage bursts beyond 2 V, while for Al [6] this is below 0.8 V, and Pt [27] below 0.6 V. It should of course be noted that while Au, Pt, and Ir are known to form chains in experiments [28] in agreement with DFT [29], it is not clear how well this model describes the smallest contacts of the metals.…”
Section: Mechanical Properties At Nonequilibrium Of 1d Chainssupporting
confidence: 93%
See 1 more Smart Citation
“…Most notably, our simulations reproduce the sequence of critical voltages observed experimentally. These experimental findings are furthermore in accordance with earlier observations showing how Au single atom wide contacts [7,27] can withstand voltage bursts beyond 2 V, while for Al [6] this is below 0.8 V, and Pt [27] below 0.6 V. It should of course be noted that while Au, Pt, and Ir are known to form chains in experiments [28] in agreement with DFT [29], it is not clear how well this model describes the smallest contacts of the metals.…”
Section: Mechanical Properties At Nonequilibrium Of 1d Chainssupporting
confidence: 93%
“…For conductors in the atomic limit the electrons essentially move through the contact without loosing energy to atomic vibrations. Therefore, single atom wide contacts and chains of a range of common metals [5][6][7][8] can sustain voltages on the order of 1 V, which corresponds to extreme current densities on the order of 10 10 A/cm 2 . The contact disruption taking place at high voltage and current is still not well understood.…”
mentioning
confidence: 99%
“…Concerning the stability of the metallic nanowire's structure at high current densities, both experimental and theoretical results are known from the literature: For Pt, it has been shown that monoatomic chains form, but a large current density tends to destabilize these monoatomic wires (Nielsen et al, 2003). Similar results were found for Al and Au, but the transition was observed to occur at high voltages (0.8 V and 2.4 V) compared to Pt (0.3-0.4 V) (Mizobata et al, 2003). It has been shown by calculations that metallic wires with "magic" conductance values are stable under large current densities (Zhang et al, 2005).…”
Section: The Structure Of Nanoscale Metallic Junctions In the Ballistmentioning
confidence: 60%
“…The appearing frequency of the 1G 0 plateaus thus represents the formation probability of the Au single-atom contacts as we discussed in our previous work. 5,6) Similarly, the 1G 0 plateau length (hereafter denoted as () indicates the ''lifetime'' of a Au singleatom contact after its formation. Since contacts of higher stability should display longer conductance plateaus, ( is also a stability measure of the Au single-atom contacts.…”
Section: Introductionmentioning
confidence: 99%